2021
DOI: 10.3390/ijms22094670
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Role of PGC1α in Bone Metabolism

Abstract: Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) is a protein that promotes transcription of numerous genes, particularly those responsible for the regulation of mitochondrial biogenesis. Evidence for a key role of PGC1α in bone metabolism is very recent. In vivo studies showed that PGC1α deletion negatively affects cortical thickness, trabecular organization and resistance to flexion, resulting in increased risk of fracture. Furthermore, in a mouse model of bone disease, PGC1α acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Mitochondrial mass and function decreased while mitophagy augmented through the ROS/FOXO1 pathway (Baldelli et al, 2014). The PGC-1α anabolic role in bone has been highlighted by a number of in vitro and in vivo studies, as recently reviewed by Buccoliero et al, (Buccoliero et al, 2021). Sirtuin 3, a mitochondrial (NAD)dependent deacetylase, is a key regulator of osteoblastic differentiation through regulation of mitochondrial function; its absence reduces the expression of superoxide dismutase 2 (Sod2), a mitochondrial molecule with antioxidant activity that permutes superoxide into the less reactive hydrogen peroxide.…”
Section: Oxidative Stress and Bone Mechanobiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial mass and function decreased while mitophagy augmented through the ROS/FOXO1 pathway (Baldelli et al, 2014). The PGC-1α anabolic role in bone has been highlighted by a number of in vitro and in vivo studies, as recently reviewed by Buccoliero et al, (Buccoliero et al, 2021). Sirtuin 3, a mitochondrial (NAD)dependent deacetylase, is a key regulator of osteoblastic differentiation through regulation of mitochondrial function; its absence reduces the expression of superoxide dismutase 2 (Sod2), a mitochondrial molecule with antioxidant activity that permutes superoxide into the less reactive hydrogen peroxide.…”
Section: Oxidative Stress and Bone Mechanobiologymentioning
confidence: 99%
“…Sirtuin 3, a mitochondrial (NAD)-dependent deacetylase, is a key regulator of osteoblastic differentiation through regulation of mitochondrial function; its absence reduces the expression of superoxide dismutase 2 (Sod2), a mitochondrial molecule with antioxidant activity that permutes superoxide into the less reactive hydrogen peroxide. PGC-1α stimulates Sirtuin 3 activity on osteogenic differentiation ( Buccoliero et al, 2021 ). How different biophysical stimuli may affect mitochondrial metabolism bone was recently reviewed by ( Wang F.-S. et al, 2021 ).…”
Section: Oxidative Stress and Bone Mechanobiologymentioning
confidence: 99%
“…Both PCG-1α and PGC-1β are known to promote mitochondrial biogenesis [ 76 , 77 ]. PCG-1α has been studied more in osteoblasts [ 78 , 79 , 80 ], and has been shown to play a role in mitochondrial metabolism. Its over-expression has been found to affect the activity of Sirtuin 3 (a mitochondrial deacetylase), which controls the increase in osteoclast number by preventing osteoblast mitochondria from decreasing its function [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that intervention for SIRT3 could improve osteoporosis, showing its potential as a treatment strategy. Exogenous supplementation or overexpression of SIRT3 could alleviate bone loss and osteoporosis ( 75 , 104 ). For example, the overexpression of SIRT3 by intravenous injection of recombinant adeno-associated virus 9 carrying SIRT3 plasmid (AAV9-SIRT3) could significantly reduce the occurrence of senile osteoporosis in the mouse model ( 75 ).…”
Section: Sirt3 As a Potential Target For The Treatment Of Osteoporosismentioning
confidence: 99%